Pengaruh Ad Relevance, Ad Saliance, Ad Engagement, Perceived Goal Impediment terhadap Advertising Avoidance dengan Motivasi sebagai Variabel Moderasi - Mentari Septynaputri Widodo; Masmira Kurniawati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2020)
The increase in internet users has made marketers move to online media. The existence of adertisements in online media has the potential to disturb consumers and cause them to avoid advertising. The purpose of this study is to find out the factors that marketers need to pay attention to in marketing their products so that the level of advertising avoidance is low. This study uses a quantitative survey, by distributing 200 questionnaires to Instagram users who have seen paid advertisements. This study uses SEM analysis techniques with the results showing that the level of ad relevance is one of the important things that must be considered by marketers, while the level of ad salience has no effect on advertising avoidance. The results also indicate the effect of ad relevance and ad salience towards advertising avoidance. The results of this study suggest that marketers need to pay attention to the level of relevance of advertisements with their users in making advertisements and also pay attention to the level of disruption of advertising by creating ads that do not interfere with someone's attention in conducting online activities.